2017
DOI: 10.1183/23120541.00018-2017
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylation/citrullination of IgG Fc in bronchiectasis, established RA with bronchiectasis and RA smokers: a potential risk factor for disease

Abstract: Bronchiectasis (BR) and smoking are risk factors for rheumatoid arthritis (RA) development. The mechanisms by which smoking and BR trigger RA are unknown, but are associated with concurrent rheumatoid factor (RF) and anti-cyclic citrullinated peptide antibody (anti-CCP) positivity. Anti-carbamylated protein antibodies (anti-CarP) have also been observed in BR patients and can be induced by smoking. Given that RF only has one antigen, immunoglobulin G (IgG) we have suggested that post-translational modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Immunoglobulins (Ig) are key molecules in adaptive immunity but post-translational deimination of Ig's has hitherto received little attention. Deimination of the IgG Fc region in patients with bronchiectasis and RA has been identified (Hutchinson et al, 2017). Furthermore, deimination of Ig's in teleost fish was recently described (Magnadóttir et al, 2019a), as well as in shark (Criscitiello et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Immunoglobulins (Ig) are key molecules in adaptive immunity but post-translational deimination of Ig's has hitherto received little attention. Deimination of the IgG Fc region in patients with bronchiectasis and RA has been identified (Hutchinson et al, 2017). Furthermore, deimination of Ig's in teleost fish was recently described (Magnadóttir et al, 2019a), as well as in shark (Criscitiello et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Ig's are key molecules in adaptive immunity and studied in diverse taxa. Post-translational deimination of Ig's and roles in Ig functions remain to be further investigated but have been related to the IgG Fc region in bronchiectasis and RA [156]. Current understanding of Ig diversity throughout the phylogenetic tree is still incomplete [157][158][159][160][161][162].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ca‐IgG was present in synovial tissue of RA patients . It has also been shown that carbamylation of IgG1 occurs in vivo , resulting in the loss of C1q binding and a subsequently reduced complement activation. These observations may have interesting implications.…”
Section: Discussionmentioning
confidence: 99%
“…Several proteins have reported to be carbamylated in vivo , e.g. albumin and alpha 1 anti‐trypsin , but interestingly also immunoglobulin (Ig)G . It has been reported that carbamylation of IgG impacts upon its capacity to activate complement .…”
Section: Introductionmentioning
confidence: 99%